Americans in waiting : the lost story of immigration and citizenship in the United States - Motomura, Hiroshi, 1953- (Oxford University Press, 2006)
In Americans in Waiting, Motomura discovers in our national past a simple yet powerful approach to immigration and citizenship. Rewriting the conventional story, Motomura uncovers how for over 150 years, many immigrants were immediately put on track to U.S. citizenship. They were entitled to overseas diplomatic protection and eligible to homestead land on the western frontier. Citizens-to-be were even allowed to vote. In sum, immigration was assumed to be a transition to; citizenship, and immigrants were future citizens--Americans in waiting. Once central to law and policy, this view has all but vanished. Beginning in the early twentieth century, the United States began to treat its immigrants in one of two ways: as signatories to a contract that sets the terms of their stay in; this country, or as affiliates who can earn rights only as they become, over time, enmeshed in the nation's life. Immigration is now seen too often as a problem to be solved, rather than a pillar of our nations strength.; A panoramic history of the past 200 years of immigration and citizenship in the United States, Americans in Waiting offers a clear lesson: only by recovering this lost history of immigration can we ensure that both current and future citizens share in the sense of belonging that is crucial to full participation in American life.